Tepoxalina sobre a função renal e as enzimas hepáticas em gatos submetidos à hipotensão com isofluorano - Freitas, Gabrielle Coelho (2014)
This study aimed to evaluate the possible renal and hepatic toxicity of tepoxalin administered before or after isoflurane-induced hypotension, as well as for five consecutive days. Twelve healthy mixed-breed cats, adult males, weighing 4.0±0.8kg were allocated into two groups. They received 25mgkg-1 of tepoxalin orally, two hours before the anesthetic procedure (PRE) or after the procedure (POST) and daily for five days. Cats were anesthetized with isoflurane and the concentration was increased until mean arterial pressure reached 40-60mmHg and kept at this level for 60 minutes. During hypotension, the physiological variables were measured at time 0 and every 10 minutes until 60 minutes, and bleeding time was measured at time 0, 30 and 60 minutes. Blood samples were drawn for a hemogram and determination of concentrations of alanine aminotransferase, alkaline phosphatase, urea, creatinine and Na+ at baseline, 24 hours, 48 hours and 7 days post-hypotension. Urine was collected at baseline, 24 hours, 48 hours and 7 days post-hypotension for determination of concentrations of creatinine, gamma-glutamyltransferase, urine specific gravity, protein, albumin and Na+. During the anesthetic procedure there were no important variations in physiological variables and bleeding time. There were differences only in fractional excretion of Na+, which was elevated at 7 days of evaluation in PRE and in the urine protein/creatinine ratio in PRE, which was higher than in POST at 24 and 48 hours post-hypotension. We conclude that tepoxalin does not cause alterations in hepatic enzymes but can cause discrete renal injury, resulting in proteinuria, in cats subjected to 60min of hypotension.